2006
DOI: 10.11606/issn.1808-0820.cali.2006.64729
|View full text |Cite
|
Sign up to set email alerts
|

Methods, metaphors, and media messages: the uses of television in conversations about the environment

Abstract: A cornerstone of media studies is that the content of communication, and the understanding derived from it, cannot be divorced from the medium through which it is transmitted: in the extreme, the media is the message. In this paper we use this insight once removed: not only as a way of thinking about the media, but also as a way of thinking about how we study the media. More specifically, we argue that the methods we use as researchers are "our media," the means by which we observe, make sense of, and communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
(14 reference statements)
2
13
1
Order By: Relevance
“…Such findings are consistent with political entertainment research, which demonstrate the influence of prime-time television on individual-level political perceptions, attitudes, opinions, and behaviors (e.g., Delli Carpini and Williams 1994;Holbrook and Hill 2005).…”
supporting
confidence: 88%
“…Such findings are consistent with political entertainment research, which demonstrate the influence of prime-time television on individual-level political perceptions, attitudes, opinions, and behaviors (e.g., Delli Carpini and Williams 1994;Holbrook and Hill 2005).…”
supporting
confidence: 88%
“…In addition to general informational sources, entertainment media sources can also influence political discussion. For example, Delli Carpini and Williams (1994) found that focus-group participants used both informational and entertainment television sources as stimuli for political talk. They argued that television plays a central role in creating an ongoing discourse about public issues because, ''.…”
Section: Political Entertainment and Political Discussionmentioning
confidence: 99%
“…150-151). These researchers presented findings based on focus group data stemming from viewings of fictional entertainment-based docudramas as well as more traditional public affairs content (e.g., Delli Carpini & Williams, 1994aWilliams, , 1994bWilliams, , 1994c. Their studies reveal that the distinctions between entertainment and public affairs content are not clear-cut and that there is strong evidence for "the political relevance of fictional media" (Delli Carpini & Williams, 1996, p. 160).…”
Section: Extant Research On Entertainment Television and Politicsmentioning
confidence: 99%